2018
DOI: 10.1167/iovs.18-24008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between CCR6+ Th17 Cells and CD34+ Fibrocytes Promotes Inflammation: Implications in Graves' Orbitopathy in Chinese Population

Abstract: The crosstalk between CCR6+ Th17 cells and fibrocytes plays a role in the pathogenesis of GO. Suppressing these interactions may be a candidate molecular target for therapeutic approaches of GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
20
0
4
Order By: Relevance
“…Fibrocytes have also been found to express those protein antigens implicated in type 1 diabetes mellitus ( 29 ). Fibrocytes cross-talk with T cells, and especially with those polarized to the Th17 paradigm, the cytokines from which appear to play important roles in driving orbital inflammation in TAO ( 30 ). IL-17A promotes the expression of regulated on activation, normal T cell expressed and secreted (RANTES, CCL5) by orbital fibroblasts, effects mediated through the CD40/CD154 (CD40 ligand) bridge ( 31 ).…”
Section: Current Understanding Of Tao Pathogenesismentioning
confidence: 99%
“…Fibrocytes have also been found to express those protein antigens implicated in type 1 diabetes mellitus ( 29 ). Fibrocytes cross-talk with T cells, and especially with those polarized to the Th17 paradigm, the cytokines from which appear to play important roles in driving orbital inflammation in TAO ( 30 ). IL-17A promotes the expression of regulated on activation, normal T cell expressed and secreted (RANTES, CCL5) by orbital fibroblasts, effects mediated through the CD40/CD154 (CD40 ligand) bridge ( 31 ).…”
Section: Current Understanding Of Tao Pathogenesismentioning
confidence: 99%
“…Taken together, these results indicated that the CD4 + Th17 cells may contribute to the immunopathological process of TAO. IL-17A was also shown to promote inflammation and fibrosis of OFs derived from TAO patients [47] and to promote the expression of regulated on activation, normal T cell expressed and secreted (RANTES) by OFs with the assistance of CD40L [50]. The study from our group demonstrated the possible interplay between Th17 cells and OFs: Th17 cells stimulated the expression of proinflammatory cytokines (IL-6, IL-8, MCP-1, TNF-α, and GM-CSF) and costimulatory molecules (CD40 and MHC II) of OFs and regulated the fibrosis and adipogenesis of OFs subsets; at the same time, OFs triggered Th17 cell differentiation and function via PGE 2 secreion[51].…”
Section: Cd4+ T Cellsmentioning
confidence: 99%
“…Both GO and control fibrocytes secreted TNF-α, IL-6, IL-8, IL-12, MCP-1, RANTES, MIP-1a, MIP-1b, CXCL10, and granulocyte colony-stimulating factor when stimulated by TSH or M22, a monoclonal TSHR-activating antibody ( 28 , 29 , 108 ). We found that GO and control fibrocytes synthesized IL-6, IL-8, and MCP-1 robustly in response to IL-17A, while GO fibrocytes had higher levels of basal and induced secretion of these cytokines than control fibrocytes ( 32 ). In a Th17 cell-fibrocyte coculture system, we found that expression of Il6 , Il8 , Mcp1 , Mip3a , Tnfa , Cxcl9 , and Cxcl10 was augmented in GO fibrocytes and their proteins had accumulated in the culture supernatants ( 32 ).…”
Section: Emerging Role Of the Th17 Immune Responsementioning
confidence: 81%
“…In a Th17 cell-fibrocyte coculture system, we found that expression of Il6 , Il8 , Mcp1 , Mip3a , Tnfa , Cxcl9 , and Cxcl10 was augmented in GO fibrocytes and their proteins had accumulated in the culture supernatants ( 32 ). Both fibrocytes and OFs as well as OF subsets delineated by CD90 express IL-17RA ( 30 , 32 , 44 ), which suggests consecutive stimulation by Th17 cells from peripheral circulation to local orbital connective tissues in GO.…”
Section: Emerging Role Of the Th17 Immune Responsementioning
confidence: 99%